Production and productivity of banana and coffee crops in Costa Rica from 1980 to 2010 - Morales Abarca, Luis Fernando (2018)
The objective of the research was to determine the data of production and productivity of banana and coffee crops in Costa Rica, in order to analyze its behavior between 1980 and 2010. The data used were supplied by the National Banana Corporation and by the Coffee Institute of Costa Rica. The main conclusion was that the banana cultivation showed a relatively stable behavior in terms of production and productivity, while the coffee crop showed unstable behavior both in production and in productivity between 1980 and 2010.